THE ROLE OF GENERAL ATTORNEY IN ERADICATION OF CORRUPTION BY CORPORATION - Satya Marta Ruhiyat; Ismansyah Ismansyah; Nani Mulyati (Diponegoro Law Review, 2019)
Considerable efforts have been made to fight corruption, however it continues to occur in Indonesia. In the present time, corruptions do not only carry out by individuals but also by corporations. However, the Criminal Code and Criminal Procedure Code do not recognize and regulate corporations as the subject of criminal acts, so that law enforcement officials, especially prosecutors, have difficulty in charging corporations. This paper tries to answer question about the role of prosecutors in the eradication of corruption by corporation based on The General Attorney Regulation Number: PER-028/A/JA/10/2014 on guidelines for prosecuting corporation. The research method employed is normative juridical method, where the data is analyzed with qualitative methodology. The General Attorney Regulation on Corporate Legal Subjects explains more apparent criteria for actions that can be attributed to the corporation. The regulation combines several theories of corporate criminal liability not only heavily rely on vicarious criminal liability theory. It also provides direction about the separation of corporate liability and director’s liability. With this guideline, the public prosecutors have clearer direction to be able to charge the corporation so that it can restore the state finances that have been harmed by the corruption act.